1914 R.I. Pub. Laws 245, ch. 1032, § 10 - (:unkn) unknown (General Publisher, 1914)
Every person who shall at any time of the year take, kill or destroy any quail or partridge by means of any trap, snare, net or spring, or who shall construct, erect, set, repair, maintain or tend any trap, snare, net or spring, for the purpose of taking, killing or destroying any quail or partridge, who shall shoot any water fowl by means or by use of any battery, swivel, punt, or pivot gun, or who shall take, kill, or pursue with intent to kill any migratory bird or insectivorous bird between sunset and sunrise, shall be fined for each offense twenty dollars.
--
Keywords: HUNTING REGULATION